A novel rare cell sorting microfluidic chip based on magnetic nanoparticle labels. (8th February 2021) - Yang, Mengzheng; Wu, Xinyu; Li, Helin; Cui, Guangchao; Bai, Zhongyang; Wang, Lin; Kraft, Michael; Liu, Guozhen; Wen, Lianggong
Abstract: Rare cell sorting with magnetic nanoparticles labels (MNPs) has been achieved by the aid of microfluidic chip, which offers an easy processing approach to sort the rare cells from a trace original sample. However, its applications have been limited in large part due to the presence of some redundant MNPs in the sorted target cells affecting the purity of sorted target cells. This paper demonstrates a novel rare cell-sorting microfluidic chip based on polydimethylsiloxane (PDMS) and the MNPs. The cell-sorting system combines the mechanisms of magnetic sorting, the geometry selection and the microfluidic manoeuvre to achieve high efficient cell sorting with real-time monitoring. The device with an array of microcolums acting as a micro-sieve is capable of separating target cells, background cells and redundant MNPs simultaneously while having the target cells from the chip outlet for subsequent studies. A finite element method simulation is implemented to quantify the experimental conditions. Green fluorescent Hela cells (Hela-GFP) with different concentrations are used in the cell sorting experiments. The experimental results show the ability of this microfluidic chip to capture MNPs-labelled target cells with high capture accuracy and the maximum recovery rate up to 99.7%. The proposed approach provides an effective and reliable tool for biological and clinical researches, and paves the way to an automated rare cell sorting system.